2012
DOI: 10.5125/jkaoms.2012.38.4.195
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical therapy and biostimulation in unfavorable bony circumstances: adjunctive therapies for osseointegration

Abstract: Dental implants using titanium have greatly advanced through the improvement of designs and surface treatments. Nonetheless, the anatomical limits and physiological changes of the patient are still regarded as obstacles in increasing the success rate of implants further, even with the enhancement of implant products. So there have been many efforts to overcome these limits. The intrinsic potential for bone regeneration can be stimulated through adjuvant treatments with the continuous improvement of implant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…The included studies used mice (n=1), rats (n=5), rabbits (n=3), and pigs (n=1) as the implant animal models [10][11][12][13][14][16][17][18][19][20]. One study investigated implants in animals in which diabetes was induced by intraperitoneal injection of streptozotocin (STZ) [13]. Another study used an implant animal model of osteoporosis [17].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies used mice (n=1), rats (n=5), rabbits (n=3), and pigs (n=1) as the implant animal models [10][11][12][13][14][16][17][18][19][20]. One study investigated implants in animals in which diabetes was induced by intraperitoneal injection of streptozotocin (STZ) [13]. Another study used an implant animal model of osteoporosis [17].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In addition, studies have reported that LIPUS can promote the osteogenesis of dental implants [10][11][12]. However, in some studies, LIPUS has shown contrasting effects on dental implants [13,14]. Therefore, whether LIPUS promotes osteogenesis around the dental implants requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…of fractures, fast recovery from the damage of soft tissue, nerve, bone, and cartilage, and relieves acute and chronic pain and inflammation (6) . Transforming growth factor-beta (TGF-β), the largest source of which is bone, has been implicated in osteoblast proliferation and differentiation and is expressed at high levels during bone growth and development with an adequate blood supply (7) .…”
Section: Oral Diagnosis 80mentioning
confidence: 99%
“…LLLT Known as cold laser, soft laser, biostimulation, or photobiomodulation, it basically exposes cell or tissue to laser or lowlevel red or near-infrared (IR) light generated from light-emitting diode. LLLT stimulates or controls cellular function to minimize the extinction of cell or tissue, accelerates the healing of fractures, fast recovery from the damage of soft tissue, nerve, bone, and cartilage, and relieves acute and chronic pain and inflammation (6) .…”
Section: Introductionmentioning
confidence: 99%